Hak Perlindungan Anak atas Identitas Diri: Perspektif Hadis dan Perundang-Undangan di Indonesia - Azzahra, Arini Nabila (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2024)
This research discusses the rights and protection of children in the aspect of self-identity by combining the perspectives of hadith and legislation in force in Indonesia. It aims to investigate how Islamic teachings through the Prophet's hadiths can synergize or conflict with existing legal provisions in protecting children's identity rights. This research is a qualitative research with descriptive-analytic method, which includes the analysis of thematic hadiths and the study of legislation governing the rights and protection of children. The results of this study indicate that from the aspects of the hadith and the law show continuity in which both are in line with what is outlined in article 5 of Law no. 23 of 2002 reinforced by Article 27 of Law no. 23 of 2002 and detailed by the existence of the Minister of Home Affairs regulation No. 73 of 2022 article 1 paragraph 3 and article 4 paragraph 2 that this name is used as an identity and has become a child's right. This is also certainly discussed in the scope of Islam through the Prophet's hadith. which is contained in the hadith narrated by Bukhari, Daud, Imam Ahmad, ad-Darimi, An-Nasai, and al-Bazzar regarding the right of children to be named with the best name without any elements of ugliness. Both have the same principle in determining the rules for giving a good name to a child as a manifestation of the laws that oversee the right to child protection.